2018
DOI: 10.1002/ccr3.1603
|View full text |Cite
|
Sign up to set email alerts
|

The ASXL1 mutation p.Gly646Trpfs*12 found in a Turkish boy with Bohring‐Opitz Syndrome

Abstract: Key Clinical MessageIn line with a recent study showing that ASXL1 mutations found in the common population cannot be ruled out as pathogenic, we have identified the ASXL1 p.Gly646Trpfs*12 mutation—present in 132 individuals in ExAC—as a very probable cause of the disease in a Bohring‐Opitz syndrome patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Missense variations in the ASXL3 gene are closely associated with autism spectrum disorders, and dysfunction variants can lead to severe psychomotor retardation [16,17]. BRPS and Bohring-Opitz syndrome (BOS) are both genetic diseases with ASXL gene abnormalities [18], which are difficult to distinguish in clinical practice and can manifest as severe psychomotor retardation, difficulty in feeding, hypotonia and microcephaly [19,20]. With the increase in cases of BRPS syndrome reported in recent years, the clinical manifestations of the two diseases have also been found to be different.…”
Section: Discussionmentioning
confidence: 99%
“…Missense variations in the ASXL3 gene are closely associated with autism spectrum disorders, and dysfunction variants can lead to severe psychomotor retardation [16,17]. BRPS and Bohring-Opitz syndrome (BOS) are both genetic diseases with ASXL gene abnormalities [18], which are difficult to distinguish in clinical practice and can manifest as severe psychomotor retardation, difficulty in feeding, hypotonia and microcephaly [19,20]. With the increase in cases of BRPS syndrome reported in recent years, the clinical manifestations of the two diseases have also been found to be different.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of children with ASXL1 variants have been reported primarily in Western countries, with only 7 cases reported in Asian countries [3 cases in China ( 7 , 8 ), 1 in India ( 9 ), 1 in Japan ( 10 ), 1 in Turkey ( 11 ) and 1 in Korea ( 12 )]. In this study, a Chinese child with BOS was found to carry an ASXL1 gene variant.…”
Section: Introductionmentioning
confidence: 99%